Carbon Storage Potential in Seagrass in the Water of Poncan Gadang Island, Sibolga City, North Sumatra Province - Sahrul Ramadhan; Zulkifli Zulkifli; Bintal Amin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Riau, 2024)
This research was conducted in February - March 2023 in Poncan Gadang Island, Sibolga City, North Sumatra Province. This study aimed to analyze the density of seagrass at each station in the research location, analyze the differences in biomass and carbon stocks in the above-ground biomass (Agb) and below-ground biomass (Bgb) parts between stations, the relationship between seagrass density and seagrass biomass and carbon stocks, and the carbon storage potential of seagrass in the waters of Poncan Gadang Island, Sibolga City, North Sumatra Province. The method used in this research was a survey method, which involved direct observations and measurements of samples in the field. The samples were then analyzed in the laboratory, and the results were described descriptively. The calculation results of carbon storage using the Loss on Ignition method for E. acoroides in Poncan Gadang Island are as follows: 14,836.07 gC/m2 at station I, 3,975.09 gC/m2 at station II, and 65,073.32 gC/m2 at station III, with a total carbon storage for E. acoroides species of 83,884.48 gC/m2. On the other hand, C. rotundata shows relatively lower results compared to E. acoroides, with 8,353.20 gC/m2 at station I, 12,056.76 gC/m2 at station II, and 7,235.53 gC/m2 at station III, with a total of 27,645.49 gC/m2. It can be concluded that the seagrass species E. acoroides has a larger biomass and carbon content compared to C.rotundata, thus making a significant contribution as a carbon sink in the study area.